Reduced Order Controller Design for Output Regulation of Adaptive Optics System - Altiner, Berk; Dogan, Mustafa; Dasdemir, Janset (IEEE, 2020)
Flexible structures occur in a large field of applications such as aerospace, biomedical, military applications. It involves many control problems ranging from vibration control to transient shape control. One of the most important applications of flexible structures is in adaptive optics. In this paper, a reduced-order controller design based on the internal model principle is proposed for deformable mirrors in adaptive optics. The finited-imensional model of the two-dimensional partial differential equation of the deformable mirror is obtained by applying the Galerkin approximation. Then, the balanced truncation method is applied to the controller of the high order finite-dimensional model of the deformable mirror. Simulation results show the success of the proposed method.
Keywords: QUADRATIC GAUSSIAN CONTROL; Engineering